Negative electrode material of sodium ion battery, preparation method of negative electrode material, negative electrode plate containing negative electrode material and sodium ion secondary battery
By mixing the biomass precursor with asphalt for preoxidation and carbonization, an efficient sodium ion battery negative electrode material is prepared, which solves the problems of low carbon production rate and insufficient sodium storage capacity of the existing electrode materials, and improves the reversible capacity and cycle stability of the battery and reduces production costs.
Patent Information
- Application Number
- CN202311355439.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-18
AI Technical Summary
The existing sodium ion battery electrode materials have low carbon production rate and insufficient sodium storage capacity, resulting in poor reversible capacity and cycle stability of the battery and high production costs.
By mixing the biomass precursor with asphalt for preoxidation and carbonization, cross-linking reactions are promoted, carbon production is improved, and an efficient sodium ion battery negative electrode material is prepared.
It improves the reversible capacity and cycle stability of sodium ion batteries, reduces production costs, and has better economic benefits.
Smart Images

Figure CN119841300A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of negative electrode materials for sodium ion batteries, and in particular, to a negative electrode material for sodium ion batteries, a preparation method thereof, a negative electrode sheet containing the negative electrode material, and a sodium ion secondary battery. Background Art
[0002] Sodium is abundant in resources and low in cost, and can be used as a supplement to lithium-ion batteries in large-scale energy storage battery systems. However, the electrochemical performance and production cost of sodium-ion batteries are mainly limited by the development of electrode materials. Therefore, the rational design of the structure of electrode materials has become the key to research.
[0003] Biomass is a suitable precursor for sodium storage materials due to its natural pore structure, large carbon interlayer spacing and high sodium storage capacity, but its carbon yield is low. Asphalt is a petrochemical product with abundant output, low cost and high carbon yield, but it becomes soft carbon after calcination and has a low sodium storage capacity. Summary of the invention
[0004] The purpose of the present invention is to provide a sodium ion battery negative electrode material and a preparation method thereof, a negative electrode plate containing the negative electrode material, and a sodium ion secondary battery. The method has a simple process and low raw material cost, and can effectively improve the carbon yield, improve the reversible capacity and cycle stability of the battery, and has better economic benefits.
[0005] In order to achieve the above object, the present disclosure provides a method for preparing a negative electrode material for a sodium ion battery in a first aspect, the method comprising the following steps:
[0006] S1: mixing the biomass precursor with asphalt, and placing the mixture in an oxygen-containing atmosphere for pre-oxidation treatment to obtain a pre-oxidized precursor;
[0007] S2: carbonizing the pre-oxidized precursor under an inert atmosphere;
[0008] Among them, in S1, the conditions of the pre-oxidation treatment include: a temperature of 150 to 350°C and a time of 12 to 48 hours; the biomass precursor includes sulfonated lignin; in S2, the conditions of the carbonization treatment include: a carbonization temperature of 1000 to 1600°C and a carbonization time of 1 to 6 hours.
[0009] Optionally, in S1, the conditions of the pre-oxidation treatment include: a temperature of 200 to 300° C. and a time of 20 to 30 hours; and a volume fraction of oxygen in the oxygen-containing atmosphere of more than 21%.
[0010] Optionally, in S1, the sulfonated lignin is selected from one or more of sodium lignin sulfonate, calcium lignin sulfonate and magnesium lignin sulfonate; the asphalt is selected from one or more of natural asphalt, petroleum asphalt, sulfonated asphalt and coal asphalt;
[0011] The mass ratio of the biomass precursor to the asphalt is 1:(0.1-9), preferably 1:(0.2-5).
[0012] Optionally, in S2, the carbonization treatment conditions include: a carbonization temperature of 1200 to 1600° C. and a carbonization time of 2 to 4 hours;
[0013] The carbonization treatment is carried out under an inert atmosphere, which includes one or more of nitrogen, helium and argon; the flow rate of the inert atmosphere is 50 to 300 mL / min, preferably 50 to 150 mL / min.
[0014] Optionally, the method further comprises: sequentially subjecting the product after the carbonization treatment to acid washing, water washing and drying.
[0015] Optionally, the pickling comprises mixing the product after the carbonization treatment with an inorganic acid; the inorganic acid is selected from one of hydrochloric acid, sulfuric acid and acetic acid; the concentration of the inorganic acid is 1 to 12 mol / L, preferably 4 to 12 mol / L.
[0016] Optionally, the water washing comprises washing the acid-washed product with water until the pH of the filtrate is 6.5 to 7.5, then filtering, and drying the filtered solid;
[0017] The drying process is carried out at a temperature of 80 to 110° C. and for a time of 12 to 24 hours.
[0018] The second aspect of the present disclosure provides a sodium ion battery negative electrode material prepared by the method described in the first aspect of the present disclosure.
[0019] Optionally, the oxygen content of the negative electrode material is 1 to 25 wt %.
[0020] A third aspect of the present disclosure provides a negative electrode plate for a sodium ion battery, the negative electrode plate comprising: a current collector, a binder and the negative electrode material for a sodium ion battery according to the second aspect of the present disclosure.
[0021] A fourth aspect of the present disclosure provides a sodium ion secondary battery, comprising the negative electrode sheet according to the third aspect of the present disclosure, a positive electrode, an electrolyte, and a separator between the positive electrode and the negative electrode sheet;
[0022] The positive electrode is one of sodium manganate, sodium cobaltate, sodium vanadium phosphate or sodium iron phosphate.
[0023] Through the above technical scheme, the method disclosed in the present invention selects low-cost sulfonated lignin as a precursor of the sodium storage material, and promotes the cross-linking reaction between the biomass molecules and the asphalt molecules to obtain a hard carbon material by mixing the biomass sulfonated lignin with asphalt for pre-oxidation and carbonization treatment. The preparation method can improve the carbon yield of the precursor, and the prepared negative electrode material can improve the reversible capacity and cycle stability of the sodium ion battery. The method disclosed in the present invention has a simple process, low raw material cost, and better economic benefits.
[0024] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0026] Figure 1 It is the XRD spectrum of the negative electrode material of Example 1 of the present disclosure.
[0027] Figure 2 This is a charge and discharge curve diagram of the negative electrode material of Example 1 of the present disclosure in the first three weeks. DETAILED DESCRIPTION
[0028] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0029] The first aspect of the present disclosure provides a method for preparing a negative electrode material for a sodium ion battery, the method comprising the following steps:
[0030] S1: mixing the biomass precursor with asphalt, and placing the mixture in an oxygen-containing atmosphere for pre-oxidation treatment to obtain a pre-oxidized precursor;
[0031] S2: carbonizing the pre-oxidized precursor under an inert atmosphere;
[0032] Among them, in S1, the conditions of the pre-oxidation treatment include: a temperature of 150 to 350°C and a time of 12 to 48 hours; the biomass precursor includes sulfonated lignin; in S2, the conditions of the carbonization treatment include: a carbonization temperature of 1000 to 1600°C and a carbonization time of 1 to 6 hours.
[0033] The method disclosed in the present invention selects low-cost sulfonated lignin and asphalt to mix, and performs a pre-oxidation treatment in an oxygen-containing atmosphere and a specific temperature. After the hard carbon precursor and the soft carbon precursor are pre-oxidized to introduce oxygen-containing functional groups, a cross-linking reaction occurs to avoid the occurrence of a molten state of the soft carbon precursor; then a carbonization treatment is performed under specific conditions to obtain a hard carbon material, which improves the feasibility of the preparation process, effectively increases the sodium storage capacity of the battery, and at the same time increases the carbon yield and reduces production costs.
[0034] According to one embodiment of the present disclosure, the mixing in S1 includes grinding mixing and ball milling mixing; the grinding mixing time is 20-40 min; the ball milling mixing time is 2 to 8 h, the rotation speed is 300 to 600 r / min, and the ball-to-material ratio is 5 to 8:1.
[0035] According to an embodiment of the present disclosure, in S1, the pre-oxidation treatment conditions include: a temperature of 200-300°C, a time of 20-30h; and a volume fraction of oxygen in the oxygen-containing atmosphere of 21% or more. The above embodiment is conducive to improving the reversible capacity and cycle stability of the battery.
[0036] According to an embodiment of the present disclosure, in S1, the sulfonated lignin is selected from one or more of sodium lignin sulfonate, calcium lignin sulfonate and magnesium lignin sulfonate; the asphalt is selected from one or more of natural asphalt, petroleum asphalt, sulfonated asphalt and coal asphalt; the mass ratio of the biomass precursor to the asphalt is 1: (0.1-9), preferably 1: (0.2-5). The above embodiment is conducive to improving the reversible capacity and cycle stability of the battery.
[0037] According to an embodiment of the present disclosure, in S2, the conditions of the carbonization treatment include: a carbonization temperature of 1200-1600°C, a carbonization time of 2-4 hours; the carbonization treatment is carried out under an inert atmosphere, and the inert atmosphere includes one or more of nitrogen, helium and argon; the flow rate of the inert atmosphere is 50-300 mL / min, preferably 50-150 mL / min. The above embodiment is conducive to improving the reversible capacity and cycle stability of the battery.
[0038] According to an embodiment of the present disclosure, the method further comprises: sequentially subjecting the product after the carbonization treatment to acid washing, water washing and drying treatment.
[0039] According to one embodiment of the present disclosure, the pickling includes mixing the product after the carbonization treatment with an inorganic acid; the inorganic acid is selected from one of hydrochloric acid, sulfuric acid and acetic acid; the concentration of the inorganic acid is 1 to 12 mol / L, preferably 4 to 12 mol / L.
[0040] According to one embodiment of the present disclosure, the water washing comprises washing the acid-washed product with water until the pH of the filtrate is 6.5-7.5, followed by filtering, and drying the filtered solid; the drying temperature is 80-110° C., and the time is 12-24 hours.
[0041] The second aspect of the present disclosure provides a sodium ion battery negative electrode material prepared by the method described in the first aspect of the present disclosure.
[0042] According to an embodiment of the present disclosure, the oxygen content of the negative electrode material is 1 to 25 wt %, preferably 5 to 20 wt %. In the present disclosure, the oxygen content of the negative electrode material is based on the oxygen content of the surface of the negative electrode material measured by XPS.
[0043] A third aspect of the present disclosure provides a negative electrode plate for a sodium ion battery, the negative electrode plate comprising: a current collector, a binder and the negative electrode material for a sodium ion battery according to the second aspect of the present disclosure.
[0044] The fourth aspect of the present disclosure provides a sodium ion secondary battery, comprising the negative electrode plate, a positive electrode, an electrolyte, and a separator between the positive electrode and the negative electrode plate as described in the third aspect of the present disclosure; the positive electrode is one of sodium manganate, sodium cobaltate, sodium vanadium phosphate or sodium iron phosphate.
[0045] According to one embodiment of the present disclosure, the electrolyte may be a conventional electrolyte in the art, for example, the electrolyte salt may be one of sodium hexafluorophosphate, sodium perchlorate, sodium bistrifluoromethanesulfonyl imide or sodium bisfluorosulfonyl imide, and the electrolyte solvent may be one or more of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGDME) and ethyl methyl carbonate (EMC); the diaphragm may be a conventional diaphragm in the art, for example, it may be one of a glass fiber diaphragm or a polyolefin porous membrane.
[0046] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0047] In the following embodiments of the present disclosure, the X-ray scanning diffractometer (XRD) used is an X-ray powder diffractometer from Philips, USA, and the method is to use a Cu target anode Kα radiation source, a step width of 0.02°, a scanning speed of 2° / min, and 2θ=10°-80°;
[0048] In the following embodiments of the present disclosure, the electrochemical performance test was carried out on a CT3001A1U-5V 5mA instrument produced by Wuhan Blue Electric Company;
[0049] XPS was performed on an instrument model Thermo Fisher Thermo ESCALAB 250;
[0050] Sodium lignin sulfonate was purchased from Beijing Innochem Technology Co., Ltd. under the brand name Innochem;
[0051] The electrolyte was a sodium ion battery electrolyte purchased from Suzhou Duoduo Reagent Co., Ltd.;
[0052] The binder is a product of Beijing Innochem Technology Co., Ltd. under the brand name Innochem;
[0053] The raw materials and reagents used in the following examples and comparative examples are all battery grade;
[0054] Unless otherwise specified, the chemical reagents used in the following examples and comparative examples are commercially available products.
[0055] Example 1
[0056] (1) Take 4 g of sodium lignin sulfonate and 4 g of petroleum asphalt powder, mix them evenly and place them in a corundum ark, then put them in a muffle furnace, and pre-oxidize them for 24 h at 250 °C in an air atmosphere to obtain a pre-oxidized precursor, which is recorded as M11-250.
[0057] (2) The above-mentioned pre-oxidized precursor was evenly placed in a corundum ark, placed in a tubular furnace, and carbonized at 1300°C for 2 hours after nitrogen was introduced. The carbonized product was pickled with 2 mol / L HCl and washed with water until the pH of the filtrate was about 7, and then filtered. The filtered solid was dried at 110°C for 24 hours to obtain a composite hard carbon material, which was recorded as M11-250-1300.
[0058] (3) Preparation of negative electrode sheets for sodium ion batteries. Weigh the above-mentioned negative electrode material for sodium ion batteries and 20% sodium alginate binder according to a mass ratio of 9:1, stir under magnetic stirring for 6 hours, allow the negative electrode material for sodium ion batteries and the sodium alginate binder to be fully mixed, and then apply them on copper foil with a scraper, with a scraper thickness of 150μm. Dry the coated copper foil in a blast drying oven at 80°C for 12 hours, then use a sheet puncher to punch the coated copper foil into electrode sheets with a diameter of 12mm, and select the electrode sheets with uniform coating and similar mass by microbalance to obtain the negative electrode for sodium ion batteries. The sodium alginate binder is prepared by first placing sodium alginate powder in a 25*25mm weighing bottle, adding an appropriate amount of deionized water, and stirring the sodium alginate and deionized water into a uniform gel solution under magnetic stirring.
[0059] (4) Assembly of sodium ion half-cell. Metallic sodium was used as the counter electrode, 1 mol / L NaPF6-DEGDME was used as the electrolyte, the above-mentioned sodium ion negative electrode sheet was used as the working electrode, and the battery separator was Whatman GF / D glass fiber separator. A CR2032 experimental button symmetrical battery was assembled in a glove box filled with argon atmosphere to evaluate the electrochemical performance of the above-mentioned sodium ion battery negative electrode material.
[0060] Example 2
[0061] (1) Take 4 g of sodium lignin sulfonate and 4 g of petroleum asphalt powder, mix them evenly and place them in a corundum ark, then put them in a muffle furnace, and pre-oxidize them for 24 h at 150 °C in an air atmosphere to obtain a pre-oxidized precursor, which is recorded as M11-150.
[0062] (2) The above pre-oxidized precursor was evenly placed in a corundum ark, placed in a tubular furnace, introduced with nitrogen, and carbonized at 1300°C for 2 hours to obtain a composite hard carbon material, which was recorded as M11-150-1300.
[0063] The preparation of the negative electrode sheet of the sodium ion battery and the assembly of the sodium ion half-cell are the same as in Example 1.
[0064] Example 3
[0065] (1) Take 4 g of sodium lignin sulfonate and 4 g of petroleum asphalt powder, mix them evenly and place them in a corundum ark, then put them in a muffle furnace, and pre-oxidize them for 24 h at 250 °C in an air atmosphere to obtain a pre-oxidized precursor, which is recorded as M11-250.
[0066] (2) The above pre-oxidized precursor was evenly placed in a corundum ark, placed in a tubular furnace, introduced with nitrogen, and carbonized at 1000°C for 2h to obtain a composite hard carbon material, which was recorded as M11-250-1000.
[0067] The preparation of the negative electrode sheet of the sodium ion battery and the assembly of the sodium ion half-cell are the same as in Example 1.
[0068] Example 4
[0069] (1) 9 g of sodium lignin sulfonate and 1 g of petroleum asphalt powder were physically mixed and placed in a corundum ark, which was then placed in a muffle furnace and pre-oxidized for 24 h at 250 °C in an air atmosphere to obtain a pre-oxidized precursor, which was recorded as M91-250.
[0070] (2) The above pre-oxidized precursor was evenly placed in a corundum ark, placed in a tubular furnace, introduced with nitrogen, and carbonized at 1300°C for 2 hours to obtain a composite hard carbon material, which was recorded as M91-250-1300.
[0071] The preparation of the negative electrode sheet of the sodium ion battery and the assembly of the sodium ion half-cell are the same as in Example 1.
[0072] Example 5
[0073] (1) Take 3 g of sodium lignin sulfonate and 2 g of petroleum asphalt powder, mix them evenly and place them in a corundum ark, then put them in a muffle furnace, and pre-oxidize them for 24 h at 250 °C in an air atmosphere to obtain a pre-oxidized precursor, which is recorded as M32-250.
[0074] (2) The above pre-oxidized precursor was evenly placed in a corundum ark, placed in a tubular furnace, introduced with nitrogen, and carbonized at 1300°C for 2 hours to obtain a composite hard carbon material, which was recorded as M32-250-1300.
[0075] The preparation of the negative electrode sheet of the sodium ion battery and the assembly of the sodium ion half-cell are the same as in Example 1.
[0076] Comparative Example 1
[0077] (1) Take 4 g of sodium lignin sulfonate and 4 g of petroleum asphalt powder, mix them evenly and place them in a corundum ark, then put them in a tubular furnace, introduce nitrogen, set a staged calcination program, calcine at 250 °C for 24 h, then raise the temperature to 1300 °C and calcine again for 2 h to obtain a composite hard carbon material, recorded as D11-250-1300.
[0078] The preparation of the negative electrode sheet of the sodium ion battery and the assembly of the sodium ion half-cell are the same as in Example 1.
[0079] Comparative Example 2
[0080] (1) Take 4 g of sodium lignin sulfonate and 4 g of petroleum asphalt powder, mix them evenly and place them in a corundum ark, then put them in a muffle furnace, and pre-oxidize them for 24 h at 100 °C in an air atmosphere to obtain a pre-oxidized precursor, which is recorded as D11-100.
[0081] (2) The above-mentioned pre-oxidized precursor was evenly placed in a corundum ark, placed in a tubular furnace, introduced with nitrogen, and a segmented calcination program was set. After calcination at 1000°C for 2h, a composite hard carbon material was obtained, which was recorded as D11-100-1000.
[0082] Comparative Example 3
[0083] (1) 4 g of sodium lignin sulfonate and 4 g of petroleum asphalt powder were physically mixed and placed in a corundum ark, which was then placed in a tubular furnace. After nitrogen was introduced, the mixture was calcined at 1000°C for 2 h to obtain a composite hard carbon material, which was recorded as D11-1000.
[0084] The preparation of the negative electrode sheet of the sodium ion battery and the assembly of the sodium ion half-cell are the same as in Example 1.
[0085] Test Example 1
[0086] The oxygen content of the negative electrode materials of Examples 1 to 5 and Comparative Examples 1 to 3 was tested by XPS, and the carbon yield was calculated. The results are shown in Table 1.
[0087] Table 1
[0088]
[0089]
[0090] The negative electrode material disclosed herein has an oxygen content of 5 to 20 wt %, a carbon yield of 57 to 65 %, a high carbon yield and low cost.
[0091] Test Example 2
[0092] The electrochemical performance of the battery cells of Examples 1 to 5 and Comparative Examples 1 to 3 was tested under the following conditions: -1 ) rate, the cut-off voltage range is 0.01V~3V, and the constant current charge and discharge are performed. The test results are shown in Table 2.
[0093] Table 2
[0094]
[0095] According to the data in Table 2, the method disclosed in the present invention has simple process conditions, effectively improves the electrochemical performance of the battery, and improves the reversible capacity and cycle stability of the battery. By comparing Example 1 and Example 2, it can be seen that within the preferred pre-oxidation temperature range of the present invention, the negative electrode material prepared by the method disclosed in the present invention has better electrochemical performance. By comparing Example 1 and Example 3, it can be seen that within the preferred carbonization temperature range of the present invention, the negative electrode material prepared by the method disclosed in the present invention has better electrochemical performance. By comparing Example 1 and Example 4, it can be seen that within the mass ratio range of the biomass precursor to asphalt disclosed in the present invention, the negative electrode material prepared by the method disclosed in the present invention has better electrochemical performance.
[0096] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0097] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0098] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: The method comprises the following steps: S1: mixing the biomass precursor with asphalt, and placing the mixture in an oxygen-containing atmosphere for pre-oxidation treatment to obtain a pre-oxidized precursor; S2: carbonizing the pre-oxidized precursor under an inert atmosphere; Among them, in S1, the conditions of the pre-oxidation treatment include: a temperature of 150 to 350°C and a time of 12 to 48 hours; the biomass precursor includes sulfonated lignin; in S2, the conditions of the carbonization treatment include: a carbonization temperature of 1000 to 1600°C and a carbonization time of 1 to 6 hours.
2. The method according to claim 1, wherein: In S1, the conditions of the pre-oxidation treatment include: a temperature of 200-300° C. and a time of 20-30 hours; and a volume fraction of oxygen in the oxygen-containing atmosphere of more than 21%.
3. The method according to claim 1, wherein: In S1, the sulfonated lignin is selected from one or more of sodium lignin sulfonate, calcium lignin sulfonate and magnesium lignin sulfonate; the asphalt is selected from one or more of natural asphalt, petroleum asphalt, sulfonated asphalt and coal asphalt; The mass ratio of the biomass precursor to the asphalt is 1:(0.1-9), preferably 1:(0.2-5).
4. The method according to claim 1, wherein: In S2, the carbonization treatment conditions include: a carbonization temperature of 1200 to 1600° C. and a carbonization time of 2 to 4 hours; The carbonization treatment is carried out under an inert atmosphere, which includes one or more of nitrogen, helium and argon; the flow rate of the inert atmosphere is 50 to 300 mL / min, preferably 50 to 150 mL / min.
5. The method according to claim 1, wherein: The method further comprises: sequentially performing acid washing, water washing and drying treatments on the product after the carbonization treatment.
6. The method according to claim 5, wherein: The pickling comprises mixing the carbonized product with an inorganic acid; the inorganic acid is selected from hydrochloric acid, sulfuric acid and acetic acid; the concentration of the inorganic acid is 1 to 12 mol / L, preferably 4 to 12 mol / L.
7. The method according to claim 5, wherein: The water washing comprises washing the acid-washed product with water until the pH of the filtrate is 6.5 to 7.5, then filtering, and drying the filtered solid; The drying process is carried out at a temperature of 80 to 110° C. and for a time of 12 to 24 hours.
8. A sodium ion battery negative electrode material prepared by the method according to any one of claims 1 to 7.
9. The sodium ion battery negative electrode material according to claim 8, wherein: The oxygen content of the negative electrode material is 1 to 25 wt %.
10. A negative electrode plate for a sodium ion battery, characterized in that: The negative electrode plate comprises: a current collector, a binder and the sodium ion battery negative electrode material according to any one of claims 8 or 9.
11. A sodium ion secondary battery, characterized in that: The invention comprises the negative electrode sheet according to claim 10, a positive electrode, an electrolyte and a separator between the positive electrode and the negative electrode sheet; The positive electrode is one of sodium manganate, sodium cobaltate, sodium vanadium phosphate or sodium iron phosphate.
Citation Information
Patent Citations
Si / C composites as anode materials for lithium ion batteries
CN104058404A
Graphene-coated porous silicon-carbon composite and preparation method therefor
CN106415898A
Negative electrode material for sodium ion battery and preparation method thereof
CN107732240A
Asphalt-based negative electrode material for sodium ion battery and preparation method and application thereof
CN109148883A
Anti-collapse drag reducer and production process thereof
CN112552884A